The Use of Damdaman Educational Play Tools to Develop Logical Thinking Skills in Children at TK Islam Bakti 63 Tanjung Harapan - Setianingsih, Erdilla Ani; Sunimaryanti, Sunimaryanti; Andre, Lesis; Siska , Widia (The Future of Education Journal, 2025)
The research problem focuses on the use of the educational game tool damdaman to enhance children's logical thinking skills, which were previously at the "emerging" stage. The objective of the research is to analyze how the damdaman educational game helps in developing children's logical thinking. This descriptive qualitative research was conducted at TK Islam Bakti 63 Tanjung Harapan over two sessions from Monday, April 14, 2025, to Tuesday, April 15, 2025. Data collection instruments included observation sheets, interviews, and documentation. Primary data sources included 11 group B children, 2 teachers, and a set of damdaman game media. Secondary data consisted of game scores, logical thinking development assessments, and information from the school principal. Data validity was ensured through triangulation.The results show that using damdaman significantly improved the children's logical thinking. (1) The use of the damdaman educational tool aligned with the expected indicators. (2) Across 8 indicators, the game proved effective in enhancing logical thinking. The majority of children reached the "very good" development category (60.8%), and none remained in the "not yet developed" category by the third observation. The game supported logical reasoning, fine motor skills, and cooperative play in an engaging way. Continued collaboration between teachers and parents is essential to sustain and evenly distribute this progress. (3) The game fostered skills such as recognizing patterns, sequencing, and planning. The "not yet developed" category decreased to 0%, while "developing as expected" and "very well developed" increased to 64.1%. at Conclusion The damdaman educational game is an effective tool to develop logical thinking skills in early childhood